Behaviour of Crohn's Disease: the risk of postoperative recurrence - Maria Daniela Dias Dinis (2021)
Introduction: Crohn's Disease (CD) classification has been changing through the years. Nowadays, Montreal Classification classifies patients using three main parameters: age at diagnosis, disease location and disease behaviour. Medical treatment has been evolving a lot, with the introduction of new therapies that allow a better disease control. However, surgery is still necessary in a lot of patients and postoperative recurrence remains an important problem. Aim: The aim of this work is to verify the existence of a relationship between CD behaviour and postoperative recurrence. Materials and methods: A literature search was conducted in the MEDLINE database, using PubMed. A total of 59 papers were included in this work. Results and discussion: When comparing nonstricturing nonpenetrating, stricturing and penetrating behaviour, the last one was significantly associated with a higher rate of postoperative recurrence in most of the analysed papers. Nevertheless, further studies are necessary to evidence this relationship. Conclusion: The goal in CD treatment is to stratify patients taking into consideration their risk factors, in order to give them the best medical and surgical treatment and the best quality of life.